Sistemi di rappresentazione. Considerazioni semiotiche sulla Typographische Gestaltung - Daniele Barbieri (Ocula)
By means of words we structure the world, following the principles of syntax. The subject-predicate relationship has undoubtedly proved effective in explaining the world, but the correspondence that underlies the idea that language represents the world is itself based symbolically and conventionally. In fact, the same phenomenon occurs whenever a system of representation such as the visual is used. Here too, in fact, the one-to-one correspondence with the represented is only partial and governed by conventions, therefore subterraneously symbolic. We can therefore think of the visual configuration as a language, endowed with its own rules only partially corresponding to those of the world to which it refers, just as happens with the word. As a consequence of this, we must think of graphic systems as symbolic systems (in the Peircean sense), which organize indexical and iconic meanings within them, just like the word. But if we conceive graphic systems in this way, it will be evident that their communicative potential can complement that of verbal systems, reinforcing and completing them, or, vice versa, hindering them. From this perspective, we will analyze the controversy on Typographische Gestaltung between Jan Tschichold and Max Bill in 1946 with its revival at the end of the 1950s between Tschichold and Emil Ruder. Both parties certainly share the opinion that graphics is a language and that its power must be contained in certain situations, however diverging both in the way in which this neutralization can be carried out and on the signification hidden in the emerging residue.